What are the indications for combined use of hydroxychloroquine and lopinavir/ritonavir, and how should treatment safety monitoring be performed? - Yu. Yu. Kiselev; V. M. Tsvetov; K. B. Mirzaev; D. A. Sychev (Izdatelstvo OKI, 2020)
Some guidelines describe combined use of hydroxychloroquine and lopinavir/ritonavir as one of the treatment alternatives for severe COVID-19, yet this treatment is not preferable. It requires careful consideration of possible interactions with other drugs, monitoring of cardiotoxicity (including QT-interval measurement), and hepatotoxicity (measurement of ASAT/ ALAT).